O artista, o fonograma e a conversão do “faça-você-mesmo” em ideologia : impactos da realocação das forças produtivas na confecção de mercadorias culturais sobre o trabalho dos músicos - Pinto, João Mário Ferreira (2021)
The structural changes in labour worldwide, derived mainly from technological advances and productive innovations given in the midst of market competition, are also expressed through music - generally conceived as a domain of culture and apart from the economic sphere - and its producers. With the advent of portable audio interfaces and innovations in the field of media, musicians began to establish a direct relationship both with the production of phonograms and with the production of their own public images - productive roles previously hegemonized by the major companies in the music industry. However, this context was accompanied in parallel by the critical devaluation of phonograms - which until then were supported by tangible forms such as CDs and vinyls - and their production, despite having been democratized, does not directly impact sales in a way they could be reverted in income for musicians. These variables stand some thoughts. In this sense, there are two: 1) how is meaning attributed to the production of phonograms by musicians in a context in which the sale of records has become unviable as a source of income?; 2) how could the public image of musicians, idealized above all in the figure of the artist, become commodities? How, finally, do these issues affect musician's social relationships?